Recycled PVC to eco-friendly materials for footwear industry: process and mechanical properties - Giovanna Marsura; Juliana Otavia Bahú; Laura Plazas Tovar; Romilda Fernandez-Felisbino; Eliezer Ladeia Gomes (Polímeros)
Abstract Recycling polyvinyl chloride (PVC) is a significant challenge for the footwear industry due to its short lifecycle and environmental impact. This study focused on recycling thermoplastic polyvinyl chloride (rPVC) from used sports shoes, sourced from a recycling company. The rPVC and thermoplastic polyurethane (TPU) were melt-blended and prepared using industrial injection molding with varying compositions. These polymer blends were then characterized morphologically, thermally, and mechanically. The recycled polymer blends demonstrated improved properties compared to the virgin polymers. Blending TPU with rPVC resulted in a material with notable hardness and enhanced abrasion resistance, with TPU/rPVC blends (67/33 and 50/50 wt.%) showing double the abrasion resistance of pure PVC. Additionally, the rPVC blend exhibited a rupture strength of 14.73 MPa, 1.6 times greater than virgin PVC. The TPU/rPVC blend (50/50 wt.%) also offered higher deformation resistance, indicating a more entangled and tensile structure. These advancements support the development of environmentally friendly footwear.